Mapeamento de Atributos Complexos e Multivalorados na Extração de Esquemas Utilizando XML - Pinto, Jose S. P. (2004)
This work describes a way to map complex and / or multivalued attributes from a visual query environment to relational databases, using XML. These attributes are usually produced after the application of integration methodologies, like ERC+, whenever exists in original databases. The mapping was produced in databases already integrated, using XML DTD files to retain knowledge about pre-integration databases, and a tool, called VIQUEN, that generates a schema visualization by use the ERC+ model. Queries and their results are both expressed in a visual environment. Express queries in a visual environment enables common users to create your own queries, since the tool hide complex database details and don't demand user knowledge about SQL statements.